Surgical Wound Healing Outcomes in Patients with Diabetes and Hypertension. A Cross-Sectional Analysis - Razwan Ashraf, Faiza Hameed, Qamber Ali Laghari, Sheema Memon, Muhammad Shahid Farooq, Muhammad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical wound healing is a complex physiological process that can be adversely affected by systemic comorbidities. Diabetes mellitus and hypertension are two highly prevalent chronic conditions known to impair tissue repair, increase infection risk, and delay recovery following surgical interventions. Objective: To evaluate and compare surgical wound healing outcomes in patients with diabetes mellitus, hypertension, both conditions combined, and those without either, in a tertiary care setting in Pakistan. Methods: A cross-sectional study was conducted at Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Mayo Hospital, Lahore, from March 2022 to April 2023. A total of 100 adult patients who underwent clean or clean-contaminated surgeries were included and divided into four groups: Group A (diabetic only), Group B (hypertensive only), Group C (both diabetic and hypertensive), and Group D (controls). Patients were followed on postoperative days 3, 7, and 14 for wound healing assessment. Outcomes measured included time to complete wound healing, incidence of delayed healing, surgical site infections (SSIs), and need for debridement. Data were analyzed using SPSS version 26.0. Results: Group C exhibited the poorest outcomes with the longest mean healing time (15.4 ± 3.1 days), highest delayed healing rate (60%), highest SSI incidence (52%), and greatest need for debridement (40%). Group A and B showed moderate impairment, while Group D had the most favorable healing profile. All differences were statistically significant (p < 0.05). Conclusion: Diabetes and hypertension, particularly in combination, significantly impair surgical wound healing. Preoperative optimization and postoperative vigilance are essential for improving outcomes in these high-risk patients. Keywords: Surgical wound healing, diabetes mellitus, hypertension, wound infection, delayed healing, comorbidities.